Assessment of Compliance with PEFC Forest Certification Indicators with Remote Sensing - Eugene Lopatin; Maxim Trishkin; Olga Gavrilova (Forests, 2016)
The majority of Finnish forests (95%) are certified by the Programme for the Endorsement of Forest Certification (PEFC). It is a worldwide leading forest certification scheme. The aim of this study is to analyze the Finnish National Standard of PEFC certification and identify the indicators that can be reliably estimated with remote sensing (RS) techniques. The retrieved data are further verified with a chosen geographical information system (GIS) application. The rapid increase in certified areas globally has created a certain level of mistrust that makes the evaluation by certification bodies (CB) questionable. Firstly, the area of the field audit is limited, and the verification results are based on sampling techniques. Secondly, the evaluation of the indicators of sustainable forest management (SFM) is based on auditor expertise and thus is prone to bias. Thirdly, the actual condition of large forest stands in Eastern and Northern Finland are not easy to determine and verify. Thus, PEFC certification in Finland, in particular, faces numerous challenges in regard to the quality of field assessment due to the intensive forest management model with a high number of annual felling sites. At the same time, small scale and scattered harvesting sites are difficult to assess. Our proposed approach combined with remote assessment reliably verified 18% of the standard and could substantially reduce the costs associated with field audits in Finland. The results from our verification analysis are spatially explicit and geographically referenced and can be published in open access portals for interested parties. Moreover, it provides improved transparency in field assessments for the PEFC certification. The novel approach proposed here requires further investigation at larger scales (e.g., national level).